Gastrointestinal Health Questionnaire for Rett Syndrome: Tool Development. Issue 3 (22nd March 2021) - Motil, Kathleen J.; Khan, Nabeel; Coon, Jennifer L.; Barrish, Judy O.; Suter, Bernhard; Pehlivan, Davut; Schultz, Rebecca J.; Glaze, Daniel G.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Objectives: We report the development and validation of a tool to assess gastrointestinal health in Rett syndrome (RTT). We hypothesized that the Gastrointestinal Health Questionnaire (GHQ) is a valid clinical outcomes measure of gastrointestinal health in RTT. Patients and Methods: We used parent interviews, surveys, and literature review to generate a questionnaire related to gastrointestinal health and function, mood and behaviors, and parental concerns for individuals with RTT. Parents of affected and unaffected individuals provided responses to the GHQ, assessed the relevance and importance of statements, and completed 5 surveys related to gastrointestinal health, child-related mood and behaviors, and parent concerns. We used multivariate item analysis, 2-sample t tests, and correlations to assess the validity of the GHQ. Results: We documented acceptable internal consistency of statements related to gastrointestinal health and function (Cronbach-α = 0.91), RTT-related mood and behaviors (Cronbach-α = 0.89), and parent concerns (Cronbach-α = 0.95) in the GHQ. We documented favorable external validity based on differences in response scores between parents of affected and unaffected individuals ( P < 0.001) and correlations in parental response scores between the GHQ and 5 validated questionnaires addressing similar issues ( P < 0.001). Conclusion: The GHQ is a valid tool for the assessment of gastrointestinal health in RTT and offers the opportunity to field test the safety and efficacy of novel drug therapies in clinical trials for individuals affected with this disorder.